IoT Application for the Development of Home Security Systems - Mah, Yuenn Wen; Mohd Hezri Mokhtar (Progress in Engineering Application and Technology, 2023)
With the rise of house-break-in cases as it becomes common in our daily life, the home security system acts as an important tool for keeping our safety and security. This project aims to develop a home security system with a combination of several locking systems with a notifications system through an IoT application. In this project, the home security system has two layers of authorization: (1) an RFID system and (2) a Digital System. For the locking system, RC522 was chosen as an RFID reader and a 4x4 Matrix Keypad was chosen as the digital input for the locking system, then they will interface with Arduino Mega 2560. For the notification and alert systems, ESP32 Cam was chosen to capture the photo and upload it to Google Drive while the LDR sensor module was chosen as the data input for the activation ESP32 Cam. If the RFID tag or password is unsuccessful, the yellow LED will turn on for the LDR sensor to detect then ESP32 Cam will capture a photo. When the folder of Google Drive updates a photo, the IFTTT bot in Telegram will send an alert message with a photo to users. The alert message with photos can help decrease the crime rate and help police offices to identify unauthorized persons more efficiently.